Gloeocantharellus thailandensis (Gomphaceae, Gomphales), a new macrofungus from southern Thailand - Nutaratat, Pumin; Khunnamwong, Pannida; Suwannarach, Nakarin; Kumla, Jaturong (Phytotaxa, 2024)
A new macrofungal species, described herein as Gloeocantharellus thailandensis, was collected from southern Thailand in 2022. This species is characterized by gomphoid basidiomata, pale red to pastel red pileus, broadly ellipsoid to elongated basidiospores with verrucose ornamentation, and abundant gleoplerous hyphae. Multi-gene phylogenetic analyses of the internal transcribed spacers (ITS) and large subunit (nrLSU) of the nuclear ribosomal DNA (rDNA), and the mitochondrial ATPase subunit 6 (atp6), also revealed that the position of G. thailandensis is well supported within the genus Gloeocantharellus, but distinct from other previously known Gloeocantharellus species. This is the first record of the genus in Thailand. Comprehensive descriptions, colour photographs, line-drawing illustrations, and comparisons with morphologically similar and phylogenetically related species are provided.